Comment on "The surface potential of a spherical colloid particle: Functional theoretical approach" - Grosse, Constantino (2006)
In a work published in this journal by Z.W. Wang, G.Z. Li, D.R. Guan, X.Z. Yi, and A.J. Lou [J. Colloid Interface Sci. 246 (2002) 302], an iterative method for the determination of the potential around a colloidal particle is presented. It is claimed that successive terms of the iteration series converge to the exact solution of the Poisson–Boltzmann equation. This claim seems to be unfounded when the analytical expressions of the iteration terms are compared with well established numerical data.